Genetically anchored fluorescent probes for subcellular specific imaging of hydrogen sulfide. Issue 4 (25th January 2016) - Chen, Jianwei; Zhao, Mingkun; Jiang, Xiqian; Sizovs, Antons; Wang, Meng C.; Provost, Christopher R.; Huang, Jia; Wang, Jin
Abstract : Imaging hydrogen sulfide (H2 S) at the subcellular resolution will greatly improve the understanding of functions of this signaling molecule. Abstract : Imaging hydrogen sulfide (H2 S) at the subcellular resolution will greatly improve the understanding of functions of this signaling molecule. Taking advantage of the protein labeling technologies, we report a general strategy for the development of organelle specific H2 S probes, which enables sub-cellular H2 S imaging essentially in any organelles of interest.